Electronic participation : 7th IFIP 8.5 International Conference, ePart 2015, Thessaloniki, Greece, August 30-September 2, 2015, Proceedings /: 7th IFIP 8.5 International Conference, ePart 2015, Thessaloniki, Greece, August 30-September 2, 2015, Proceedings. (2015) - Unknown
No abstract available